A critical study on the effectiveness of the law and the enforcement authority in eradicating organised crime syndicate in Malaysia / Ahmad Imran Mohd Azlan … [et al.] - Mohd Azlan, Ahmad Imran; Abdul Kadir, Khairul Kabir; Nik Ibrahim, Nik Syafiqah; Ahmad Shafique Selvarajah, Nur Syafiah Athirah (Faculty of Law, 2014)
Organised crime group according to Section 130U of Penal Code (Act 574) means two or more people acting together with the aim of committing one or more serious offences in order to obtain material benefit, power or influence. Malaysia has many laws and authority that govern the organized crime syndicate in Malaysia. The existing laws include Penal Code (Act 574), Criminal Procedure Code (Act 593), Societies Act 1966 and Prevention of Crime Act (Amendment and Extension) 2013. Not only that, a special anti-crime operation called Ops Cantas Khas was created in 2013. However, the effectiveness of these laws and authority are questioned as countless violent offences occurred in Malaysia is either a direct or indirect result of organised crime. In order to further combat organised crime syndicate, stronger enforcement of the law as well as stricter authority is needed in hope of eliminating the organised crime syndicate entirely. In short, the law governing the organised crime syndicate must be met with a more tangible response. Therefore, this research includes comparing the laws in Malaysia with other countries, mainly Hong Kong and United States of America as these countries have an effective way to combat organised crime. It is hoped that this research will provide answers as to the main reason why organized crime syndicates still exist despite various laws in Malaysia and the necessary steps to be taken to efficiently enforce the relevant laws to combat the crime syndicate in Malaysia.